2016
DOI: 10.1088/0964-1726/25/5/055018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour and functional properties of porous Ti-45 at. % Ni alloy produced by self-propagating high-temperature synthesis

Abstract: The mechanical behaviour and shape memory effects were studied in the porous Ti-45.0 at. % Ni alloy produced by self-propagating high-temperature synthesis. It is shown that the porous Ti-45.0 at % Ni alloy is deformed by the same mechanisms as a cast Ti 50 Ni 50 alloy. At low temperatures, the deformation of the porous alloy is realised via martensite reorientation at a low yield limit and by dislocation slip at a high yield limit. At high temperatures (in the austenite B2 phase) the porous Ti-45.0 at % Ni al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Comparison of the experimental results with the literature data confirms the fact that porous alloys obtained by the SHS method have stiffness, strength and plasticity values under compression that are not lower than the values obtained by other authors [1,[20][21][22][23][24][25][26] on titanium-containing materials, obtained by other methods. In [1], Ti6Al4V-based alloys have porosity ranging within 60-85% with pore sizes starting from 250 μm in case of the elastic modulus variation from 0.5 to 3 GPa.…”
Section: Results Of Quasi-static Uniaxial Compression Of the Porous T...supporting
confidence: 82%
“…Comparison of the experimental results with the literature data confirms the fact that porous alloys obtained by the SHS method have stiffness, strength and plasticity values under compression that are not lower than the values obtained by other authors [1,[20][21][22][23][24][25][26] on titanium-containing materials, obtained by other methods. In [1], Ti6Al4V-based alloys have porosity ranging within 60-85% with pore sizes starting from 250 μm in case of the elastic modulus variation from 0.5 to 3 GPa.…”
Section: Results Of Quasi-static Uniaxial Compression Of the Porous T...supporting
confidence: 82%
“…3 b. The curve indicated by the dashed line illustrates the experimental data [17], the solid line corresponds to the numerical results. The non-linear character of the theoretical curves is due to the non-simultaneous start of different deformation mechanisms in beams with different dimensions.…”
Section: Resultsmentioning
confidence: 95%
“…3 a shows the simulated stress-strain diagrams of isothermal compression up to 350 MPa with intermediate unloadings of the samples with a porosity of 60 % in the martensitic state at temperatures 25, 45, and 65°C. The dashed lines indicate the experimental curves [17]. The stress-strain diagrams for porous TiNi sample under compression in the austenitic state at temperature 160°C is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies investigated the deformation behavior of porous TiNi compounds for the past ten years [29,63,69,70]. Most have reported that the task is fascinating and actual, but still challenging.…”
Section: Characteristics Of Porous Shs Tinimentioning
confidence: 99%